2012
DOI: 10.1016/j.jhazmat.2011.10.057
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cerium dioxide, titanium dioxide, silver, and gold nanoparticles on the activity of microbial communities intended in wastewater treatment

Abstract: Growth in production and use of nanoparticles (NPs) will result increased concentrations of these in industrial and urban wastewaters and, consequently, in wastewater-treatment facilities. The effect of this increase on the performance of the wastewater-treatment process has not been studied systematically and including all the microbial communities involved in wastewater treatment. The present work investigates, by using respiration tests and biogas-production analysis, the inhibitory effect of four different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
104
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(120 citation statements)
references
References 48 publications
9
104
1
6
Order By: Relevance
“…These nanoparticles have been used as fuel catalyst to reduce harmful emission from engine combustion. But researchers found that NPs cause inhibition effects on biodegradation, nitrification and AD process [33,61]. The adverse effect, inhibition or enhancement of energy conversion, depends upon the particle size, concentration and time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These nanoparticles have been used as fuel catalyst to reduce harmful emission from engine combustion. But researchers found that NPs cause inhibition effects on biodegradation, nitrification and AD process [33,61]. The adverse effect, inhibition or enhancement of energy conversion, depends upon the particle size, concentration and time.…”
Section: Resultsmentioning
confidence: 99%
“…So, whether or not nanoparticles in sludge can hinder the sludge dewatering process, toxicity of nanoparticles in sludge is eliminated during AD or it causes inhibition effect on bacteria and plants À these are still questions that need to be answered. [33] In terms of ecotoxicity, there has been significantly greater focus on aquatic rather than terrestrial species, and very little work has focused on terrestrial plants. Some studies have reported the toxic effects of nanoparticles on the germination and/or root growth of some plant species.…”
Section: Nanoparticles With Microorganismmentioning
confidence: 99%
“…Tablo 2'de nanopartikül maddelerin anaerobik mikroorganizmalar üzerine etkileri hakkında literatürde mevcut çalışmalar özetlenmiştir. CeO2, TiO2, Ag ve Au nanopartiküllerinin atıksu arıtma tesislerinde kullanılan mikroorganizma kültürleri üzerindeki etkileri incelenmiştir [20]. Hem aerobik hem de anaerobik mikroorganizmaların maruz kaldığı etkilerin araştırıldığı çalışmada anaerobik mikroorganizmalar için mezofilik ve termofilik test ortamları oluşturulmuştur.…”
Section: Nanopartiküllerin Anaerobik Parçalanma Prosesine Etkileriunclassified
“…Hem mezofilik hem de termofilik koşullar altında TiO2, Au ve Ag nanopartiküllerinden kaynaklanan inhibisyon etkisi gözlenmemiştir. Bununla birlikte, TiO2 nanopartiküllerin bulunduğu termofilik koşullarda biyogaz üretiminde %10 artış tespit edilmiştir [20]. incelemede Ag nanopartiküllerin mikroorganizma popülasyonunda herhangi bir değişikliğe yol açmadığı görülmüştür.…”
Section: Nanopartiküllerin Anaerobik Parçalanma Prosesine Etkileriunclassified
“…[24][25][26][27][28][61][62][63][64][65][66][67][68][69][70] Specifically, nanoceria has been reported to be toxic to microbial and algal cells, which is correlated with the nanoparticle adsorption on the cell membrane. [64][65][66]68 It can also be toxic to mammalian cells, although the nanotoxicity mechanism appears to be different, including a rapid intracellular uptake 15 .…”
Section: Fig 5 Optical Images Of Individual Chondrocyte Cellsmentioning
confidence: 99%